Smart Transformation of Bank Branches: Another Stepin Industry 4.0 - Xiaoyan; Liu (International Journal of Psychosocial Rehabilitation, 2020)
With the advent of the digital age, as a traditional and central channel of financial services, banks are facing unprecedented shocks and challenges. The development of technology, the general improvement of consumers’ education level and the diversification of Information channels, all of these factors have prompted great changes in customers’ consumption habits and behaviors. At the same time, Internet giants and P2P platforms quickly enter the field of financial services that bring new challenges to traditional banking business. Different from the bank’s trading model, these Internet financial companies establish direct contact with consumers through social networks or e-commerce, and launch financial products and services, which greatly increase consumer “stickiness”. Due to the high cost of traditional branches and the booming of other digital channels (online banking and mobile banking), physical branches become the most threatened areas in the digitization process. In order to break through the dilemma, the physical branch is also looking for its own position in the transformation iteration. For example, some banks have chosen to establish smart branches while some banks have closed physical branches substantially. So far, there are some controversies in management. Therefore,the purpose of this research is to clarify the significance of physical branches and point out that "smart" is the development direction of physical branches. In practice, the physical branch is still an important part of the banking system in the information age, as the terminal window of the brand image’s display and the integration platform for service customers. Smart branch is based on the Internet of things and integrates recognition technology, robot-adviser, VR technology, and other smart technologies. This kind of advanced smart service brings the client to customers’ excellent experiencesuch as seamless and timely response. Therefore, this study believes that physical branches should exist, and they should follow the trend of digitization and actively transform to the direction of smart branches, that is the inevitable stage of the development of banking industry.